Genome Editing in Cotton with the CRISPR/Cas9 System - Gao, Wei; Long, Lu; Tian, Xinquan; Xu, Fuchun; Liu, Ji; Singh, Prashant K.; Botella, Jose R.; Song, Chunpeng (Frontiers in Plant Science, 2017)
Genome editing is an important tool for gene functional studies as well as crop improvement. The recent development of the CRISPR/Cas9 system using single guide RNA molecules (sgRNAs) to direct precise double strand breaks in the genome has the potential to revolutionize agriculture. Unfortunately, not all sgRNAs are equally efficient and it is difficult to predict their efficiency by bioinformatics. In crops such as cotton (Gossypium hirsutum L.), with labor-intensive and lengthy transformation procedures, it is essential to minimize the risk of using an ineffective sgRNA that could result in the production of transgenic plants without the desired CRISPR-induced mutations. In this study, we have developed a fast and efficient method to validate the functionality of sgRNAs in cotton using a transient expression system. We have used this method to validate target sites for three different genes GhPDS, GhCLA1, and GhEF1 and analyzed the nature of the CRISPR/Cas9-induced mutations. In our experiments, the most frequent type of mutations observed in cotton cotyledons were deletions (~64%). We prove that the CRISPR/Cas9 system can effectively produce mutations in homeologous cotton genes, an important requisite in this allotetraploid crop. We also show that multiple gene targeting can be achieved in cotton with the simultaneous expression of several sgRNAs and have generated mutations in GhPDS and GhEF1 at two target sites. Additionally, we have used the CRISPR/Cas9 system to produce targeted gene fragment deletions in the GhPDS locus. Finally, we obtained transgenic cotton plants containing CRISPR/Cas9-induced gene editing mutations in the GhCLA1 gene. The mutation efficiency was very high, with 80.6% of the transgenic lines containing mutations in the GhCLA1 target site resulting in an intense albino phenotype due to interference with chloroplast biogenesis.